Effectiveness of Platelet-Rich Plasma and Bone Marrow Aspirate Concentrate as Treatments for Chronic Hindlimb Proximal Suspensory Desmopathy - Maleas, Grigorios; Mageed, Mahmoud (Frontiers in Veterinary Science, 2021)
This retrospective study aimed to evaluate the clinical effect of bone marrow aspirate concentrate (BMAC) and leukocyte rich PRP (LR-PRP) compared to horses undergoing controlled exercise alone in horses with >3 months proximal suspensory desmopathy in hindlimbs (HPSD). Nighty-three horses were divided into three groups according to the treatment: a control (n = 22), LR-PRP (n = 46) and BMAC (n = 25) group. Lameness and ultrasound scores were recorded before treatment (T0) and at six months (T1) post-treatment. Records horses considered sound at evaluation and level of performance were additionally registered at 12 months (T2) and 18 months (T3) after treatment. The BMAC cytology profiles from 22 horses were also analysed and compared to clinical outcomes. The results at T1 showed that 9% (2/22) of the horses in the control group were sound compared to 59% (25/46) and 84% (21/25) in the LR-PRP and BMAC groups, respectively. Additionally, ultrasound scores at T1 in the BMAC and LR-PRP groups were improved in comparison with the control group (p = 0.02). At T2, 68% of the horses in the BMAC group and 39% of the horses in the LR-PRP group had returned to the previous performance level. At T3, a significantly higher percentage of horses in the LR-PRP (43%) and BMAC (72%) group were sound when compared to the control (4.6%) group (p = 0.02). Similarly, at T3, significantly more horses of the BMAC (16/25) and of the LR-PRP (15/46) group had returned to the previous or a higher performance level compared to the control (1/22) group (p = 0.01). No correlation was found between long-term clinical outcome and cytology profiles in the BMAC group. In conclusion, long-term outcomes of treatment with LR-PRP or BMAC are significantly better than conventional treatment of the hindlimb chronic PSD in horses. Additionally, BMAC yielded better lameness scores than LR-PRP at short- and long-term follow-up.